2002
DOI: 10.1093/brain/awf231
|View full text |Cite
|
Sign up to set email alerts
|

Disabled readers suffer from visual and auditory impairments but not from a specific magnocellular deficit

Abstract: The magnocellular theory is a prominent, albeit controversial view asserting that many reading disabled (RD) individuals suffer from a specific impairment within the visual magnocellular pathway. In order to assess the validity of this theory we tested its two basic predictions. The first is that a subpopulation of RD subjects will show impaired performance across a broad range of psychophysical tasks relying on magnocellular functions. The second is that this subpopulation will not be consistently impaired ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
136
1
9

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(157 citation statements)
references
References 54 publications
10
136
1
9
Order By: Relevance
“…Rate and accuracy of phonological decoding were assessed with single nonwords written with diacritics (shallow orthography). Reading rate was also assessed for an academic level passage written without diacritics (deep orthography, for a description of Hebrew orthography see [4]). Other tests included: single word reading, spelling, speed of naming letters and numbers (RAN [16]; 30 dyslexic, 22 control) and phonological awareness (Spoonerism task).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Rate and accuracy of phonological decoding were assessed with single nonwords written with diacritics (shallow orthography). Reading rate was also assessed for an academic level passage written without diacritics (deep orthography, for a description of Hebrew orthography see [4]). Other tests included: single word reading, spelling, speed of naming letters and numbers (RAN [16]; 30 dyslexic, 22 control) and phonological awareness (Spoonerism task).…”
Section: Methodsmentioning
confidence: 99%
“…Although many studies found poorer performance in dyslexics than in normal readers [4,7,10], others did not [11]. Two inter-study differences may underlie this variance.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…A hypothesis suggesting that dyslexics have a specific impairment within the visual magnocellular pathway (Stein & Walsh, 1997) has been largely discredited (Amitay, Ben-Yehudah, Banai, & Ahissar, 2002). Over-activation of Broca's area in dyslexics may represent increased effort in performing language related tasks (Shaywitz et al, 1998).…”
Section: Functional Mri Studiesmentioning
confidence: 99%